How to talk about genome editing. Issue 1 (25th April 2018) - Starr, Sandy
Abstract: Background: Human genome editing is an area of growing prominence, with many potential therapeutic applications. Sources of data: A project by two UK charities, whose participants included fertility sector patients and practitioners and also people affected by genetic disease and rare disease. Scientific research into, and wider discussion of, genomics and genome editing. Areas of agreement: There is a need for improved public and professional understanding of genome editing. Areas of controversy: The way genome editing is discussed is often inconsistent and confusing. Simply defining and explaining the term 'genome' can present challenges. Growing points: There are approaches that lend themselves to achieving greater clarity and coherence in discussion of genome editing. Areas timely for developing research: People's understanding should ideally be able to withstand and evolve alongside current developments in genome editing, rather than being tied firmly to specific aspects of genome editing (which may in future be supplanted).